Cross-border Mobility for Electric Vehicles: Selected results from one of the first cross-border field tests in Europe - Schäuble, Johannes [Hrsg.]Jochem, Patrick [Hrsg.]Fichtner, Wolf [Hrsg.] (KIT Scientific Publishing, 2016)
This book provides selected results from the accompanying research of the project CROME. The vision of the project was to create and test a safe, seamless, user-friendly and reliable mobility with electric vehicles between France and Germany as a prefiguration of a pan-European electric mobility system. Major aims were contributions to the European standardisation process of charging infrastructure for electric mobility and corresponding services, and to provide an early customer feedback.